Not all species will migrate poleward as the climate warms: The case of the seven baobab species in Madagascar. (14th September 2021) - Tagliari, Mario M.; Danthu, Pascal; Leong Pock Tsy, Jean‐Michel; Cornu, Cyrille; Lenoir, Jonathan; Carvalho‐Rocha, Vítor; Vieilledent, Ghislain
Abstract: It is commonly accepted that species should move toward higher elevations and latitudes to track shifting isotherms as climate warms. However, temperature might not be the only limiting factor determining species distribution. Species might move to opposite directions to track changes in other climatic variables. Here, we used an extensive occurrence data set and an ensemble modelling approach to model the climatic niche and to predict the distribution of the seven baobab species (genus Adansonia ) present in Madagascar. Using climatic projections from three global circulation models, we predicted species' future distribution and extinction risk for 2055 and 2085 under two representative concentration pathways (RCPs) and two dispersal scenarios. We disentangled the role of each climatic variable in explaining species range shift looking at relative variable importance and future climatic anomalies. Four baobab species ( Adansonia rubrostipa, Adansonia madagascariensis, Adansonia perrieri¸ and Adansonia suarezensis ) could experience a severe range contraction in the future (>70% for year 2085 under RCP 8.5, assuming a zero‐dispersal hypothesis). For three out of the four threatened species, range contraction was mainly explained by an increase in temperature seasonality, especially in the North of Madagascar, where they are currently distributed. In tropical regions, where species are commonly adapted to low seasonality, we found that temperature seasonality will generally increase. It is, thus, very likely that many species in the tropics will be forced to move equatorward to avoid an increase in temperature seasonality. Yet, several ecological (e.g., equatorial limit, or unsuitable deforested habitat) or geographical barriers (absence of lands) could prevent species to move equatorward, thus increasing the extinction risk of many tropical species, like endemic baobab species in Madagascar. Abstract : We show that four out of the seven baobab species existing in Madagascar are threatened with extinction because of climate change. Among the four threatened species, three are adapted to low seasonality and should experience a dramatic range contraction by 2100 because of a strong increase in temperature seasonality. These three baobab species are expected to move equatorward to track change in temperature seasonality. We also show that a strong increase in temperature seasonality is expected throughout the tropics. Consequently, many tropical species adapted to low temperature seasonality should be forced to move equatorward to find a suitable climate. However, ecological and geographical barriers could impede tropical species dispersal and put them at risk of extinction.